Effect of Chlorine on Giardia lamblia Cyst Viability - Jarroll, Edward L. (1981)
The effect of chlorine concentration on Giardia lamblia cyst viability was tested under a variety of conditions. The ability of Giardia cysts to undergo excystation was used as the criterion of viability. The experimental variables employed included temperature (25, 15, and 5°C), pH (6, 7, and 8), chlorine-cyst contact time (10, 30, and 60 min), and chlorine concentration (1 to 8 mg/liter). In the pH range studied, cyst survival generally was observed to increase as buffer pH increased. Water temperature coupled with chlorination proved to be important in cyst survival. Results of these experiments at the three temperatures studied can be summarized as follows: at 25°C, exposure to 1.5 mg/liter for 10 min killed all cysts at pH 6, 7, and 8. At 15°C, 2.5 mg of chlorine per liter for 10 min killed all cysts at pH 6, but at pH 7 and 8 small numbers of cysts remained viable after 30 min but not after 60 min. At 5°C, 1 mg of chlorine per liter for 60 min failed to kill all the cysts at any pH tested. At this temperature, 2 mg of chlorine per liter killed all cysts after 60 min at pH 6 and 7, but not at pH 8. A chlorine concentration of 4 mg/liter killed all the cysts at all three pH values after 60 min, but not after 30 min. A chlorine concentration of 8 mg/liter killed all Giardia cysts at pH 6 and 7 after contact for 10 min, and at pH 8 after 30 min. This study points up the role of temperature, pH, and chlorine demand in the halogen treatment of drinking water to destroy cysts. It also raises an epidemiological problem, namely: low water temperatures, where killing of Giardia requires relatively high chlorine concentrations and long contact times, are (i) to be expected in many areas where epidemic waterborne giardiasis has been reported and (ii) particularly conducive to the long-term survival of Giardia cysts.